INTERPRETASI LAGU NIGHT RHYTHM KARYA LEE RITENOUR DALAM ANSAMBEL BAND PADA RESITAL TUGAS AKHIR - Entol Hikmat Khalifatuddien (Saraswati)
This article refers to the one of the repertoire presented by the author's undergraduate recital of Pop-Jazz, as the concept of study in the thesis of author, that song is Night Rhythm by Lee Ritenour. Issues discussed by utilizing musicological method in this article is about how the interpretation in the presentation of this repertoire with applying the principles of ensemble band. In this study, the interpretation of Night Rhythm song is supported by the application of the principles of ensemble band.Keyword: Interpretation, Ensambel band, Night Rhythm.